Pengaruh Content Marketing dan Electronic Word of Mouth Terhadap Loyalitas Konsumen Produk Lokal Kecantikan Dengan Brand Image Sebagai Variabel Mediasi - Fuad Alfaridzi Setiawan; Heida Ifkari Safitri (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
The familiar global market means that imported products are starting to put pressure on domestic products. The Indonesian cosmetics market is a special attraction for foreign manufacturers to trade their goods there. This needs to be a concern for local beauty producers to maintain the consumer loyalty they already have. The aim of this research is to determine customer loyalty towards local beauty products based on the influence of content marketing, electronic word of mouth, and brand image as mediating variables. This research is quantitative research. Sampling was carried out using a purposive sampling technique, and data collection was carried out using a questionnaire. The number of respondents studied was 200 respondents. The data analysis carried out was descriptive analysis (SPSS) and Structural Equation Model-Partial Least Square. 1) Content marketing has a positive effect on consumer loyalty; 2) Electronic word of mouth has a positive effect on consumer loyalty; 3) Content marketing has a positive effect on brand image; 4) Electronic word of mouth has a positive effect on brand image; 5) Brand image has a positive effect on consumer loyalty; 6) Content marketing indirectly influences consumer loyalty through brand image as a mediating variable; 7) Electronic word of mouth indirectly influences consumer loyalty through brand image as a mediating variable.